2018
DOI: 10.1002/jcph.1313
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Overview of the Clinical Pharmacokinetics of Clobazam

Abstract: Clobazam (CLB) is a 1,5‐benzodiazepine that has been widely used as an anxiolytic and antiseizure drug (ASD) since it was first synthesized over 50 years ago. CLB was approved in the United States in 2011 as adjunctive therapy for seizures in patients ≥2 years old with Lennox‐Gastaut syndrome. CLB pharmacokinetics (PK) have been studied in single‐ and multiple‐dose administrations in healthy subjects. Salient features include high bioavailability, linear PK, and negligible effects from coadministration of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
(204 reference statements)
0
12
0
2
Order By: Relevance
“…N-desmethylclobazam and its metabolites account for 94% of the total drug-related components in urine, while unchanged CLB accounts for 2%. 2,8 Even in the presence of renal dysfunction, the manufacturer does not recommend dosage adjustment in patients with mild or moderate impairment. 1 Roberts et al 9 found that CLB and NCLB concentrations did not reach "toxic" values in adults with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…N-desmethylclobazam and its metabolites account for 94% of the total drug-related components in urine, while unchanged CLB accounts for 2%. 2,8 Even in the presence of renal dysfunction, the manufacturer does not recommend dosage adjustment in patients with mild or moderate impairment. 1 Roberts et al 9 found that CLB and NCLB concentrations did not reach "toxic" values in adults with end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…CLB is mainly metabolized by cytochrome P450 enzymes. Its major metabolite, NDMCLB, is an active metabolite and has a longer half-life than the parent drug (59-74 h vs. 36-42 h, respectively), significantly contributing to CLB pharmacological activity [25]. This paper describes a rapid, reliable, and simple method for measuring CLB and its metabolite NDMCLB in human plasma and the time needed for sample analysis is only 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…CLB represents linear pharmacokinetics. The therapeutic range for CLB is 0.03-0.30 mg/L and 0.3-3.0 mg/L for N-CLB [19,29,35,86]. The drug undergoes extensive metabolism in the liver to an active metabolite N-desmethylclobazam (N-CLB) and other metabolites (Table 1).…”
Section: Clobazammentioning
confidence: 99%